Antibiotics Susceptibility and Resistance Pattern of Bacteria Pathogens of UTIs among Pregnant Women in Nigeria - Adeyemi, Akobi Oliver; Gideon, Emumwen Evbaziegbere; Ogochukwu, Uzoigwe Eunice; Osarodion, Uyigue Paulinus; Chimerenma, Akobi Evelyn; Ajibola, Akinola Sikiru; Favour, Emumwen Ehiosu (Current Overview on Disease and Health Research Vol. 3, 2022)
The purpose of this study was to report on the antibiotic susceptibility and resistance pattern of bacteria pathogens of UTIs in pregnant women in Bida, North Central, Nigeria, as well as to determine the extent of resistance of these bacteria pathogens to these drugs in the community. The research was a retrospective studies carried out between August 2012 to December 2013. For this investigation, 516 bacterial pathogens that were identified at the Medical Microbiology Department of Federal Medical Centre, Bida, Niger State, North Central, Nigeria. Out of this 516 bacteria isolates, Escherichia coli 342(66.3%) was the most predominant followed by Staphylococcus aureus 162(31.4%), Klebsiella specie 6(1.2%), Serratia marcescens 4(0.8%) and the least prevalence Proteus specie 2(0.4%). Overall susceptibility pattern of uropathogens to Nitrofurantoin was (58.5%) and Nalidixic acid (34.5%) and both were statistically significant (Nitrofurantoin p=0.000, Mean value 75.5 and Nalidixic acid p=0.000, Mean value 44.5). The most prevalent strain of Escherichia coli has susceptibility rates to Nitrofurantoin and Nalidixic Acid of 61.4 percent and 42.1 percent, respectively. Before giving a patient any medications, a routine microbiological analysis and susceptibility test should be conducted. The government should enact policies that discourage the sale and use of antimicrobials without a prescription from authorised medical personnel.